Analysis of the Moodle application instrument with the exam browser to measure online learning outcomes in digital communication simulation subjects in class X Multimedia at SMKN 1 Lamongan - Arif, Muhammad Nur; Sumbawati, Meini Sondang; Buditjahjanto, I Gusti Putu Asto; Rijanto, Tri (International Journal for Educational and Vocational Studies, 2021)
This study was used to determine the feasibility of the instrument before being used for further research. This study uses a quasi-experimental research design. In this study, to calculate the validation results from three validators who are experts in their fields using the arithmetic average, the validated instruments are: (1) the validation questions get 87.51% results; (2) validation of attitude assessment got 90.27% results; (3) validation of student skills assessment got 92.71% results; (4) the validation of the assessment of the Learning Implementation Plan (RPP) got 92.16% results; (5) validation of the syllabus assessment got 86.95% results; (6) Moodle assessment validation with browser exam got 87.25% results; (7) the validation of the student learning module assessment got 84.71% results; (8) the validity of the items is declared valid; (9) the reliability of the items is declared reliable; (10) the differentiating power of the items has very good criteria; and (11) the level of difficulty of the items showed that of the 40 items tested, the percentage was 35% (14 questions) in the medium category, and 65% (26 questions) in the easy category. From the calculation results that have been mentioned, the Moodle application instrument with a browser exam to measure online learning outcomes is declared feasible and can be used for further research.